1975
DOI: 10.21236/ada020217
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Estimation of Entropy in the Non-Parametric Case

Abstract: Assume that N mutually independent observations have been taken from the population specified by Then the entropy is defined byThe natural estimator H = -, • log ^p is shown to have certain J deficiencies when the number of classes is large relative to the sample size or is infinite. A procedure based on quadrature methods is proposed as a means of circumventing these deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 3 publications
1
48
0
1
Order By: Relevance
“…(MacArthur, 1955;Goodman, 1975;McCann, 2000;Ives and Carpenter, 2007). Other important research questions include 120 the sources of diversity (Tsimring et al, 1996;De'ath, 2012), extensions of diversity to include a concept of species distance Chao et al (2010); Leinster and Cobbold (2012);Feoli (2012);Scheiner (2012), and techniques for measuring diversity (Chao and Shen, 2003;Schmera and Podani, 2013;125 Gotelli and Chao, 2013), despite the well-known difficulties in estimating entropy in an unbiased fashion (Harris, 1975;Paninski, 2003). Beyond ecology, the study of diversity is also important in economics ( D i of order q for varying q, shown for three different particles (inset square plots).…”
Section: N Riemer and M West: Quantifying Aerosol Mixing Statementioning
confidence: 99%
See 1 more Smart Citation
“…(MacArthur, 1955;Goodman, 1975;McCann, 2000;Ives and Carpenter, 2007). Other important research questions include 120 the sources of diversity (Tsimring et al, 1996;De'ath, 2012), extensions of diversity to include a concept of species distance Chao et al (2010); Leinster and Cobbold (2012);Feoli (2012);Scheiner (2012), and techniques for measuring diversity (Chao and Shen, 2003;Schmera and Podani, 2013;125 Gotelli and Chao, 2013), despite the well-known difficulties in estimating entropy in an unbiased fashion (Harris, 1975;Paninski, 2003). Beyond ecology, the study of diversity is also important in economics ( D i of order q for varying q, shown for three different particles (inset square plots).…”
Section: N Riemer and M West: Quantifying Aerosol Mixing Statementioning
confidence: 99%
“…Other important research questions include the sources of diversity (Tsimring et al, 1996;De'ath, 2012), extensions of diversity to include a concept of species distance Chao et al (2010); Leinster and Cobbold (2012);Feoli (2012);Scheiner (2012), and techniques for measuring diversity (Chao and Shen, 2003;Schmera and Podani, 2013;Gotelli and Chao, 2013), despite the well-known difficulties in estimating entropy in an unbiased fashion (Harris, 1975;Paninski, 2003). Beyond ecology, the study of diversity is also important in economics (Garrison and Paulson, 1973;Hannah and Kay, 1977;Attaran and Zwick, 1989;Malizia and Ke, 1993;Drucker, 2013), immunology (Tsimring et al, 1996), neuroscience (Panzeri and Treves, 1996;Strong et al, 1998), and genetics (Innan et al, 1999;Rosenberg et al, 2002;Falush et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation of the direct estimate H Dir can be expressed as (Harris, 1975): where again, the Ο(N −1 ) term is independent of the distribution. Thus we focus on distributions that reduce the Ο(N −½ ) term.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This term is smaller for higher entropy distributions, reaching zero for the uniform distribution. When comparing two distributions with equal N and K, the † A straight forward expansion of the bias to higher order: (Harris, 1975) reveals that the Ο(N −2 ) term does depend on the distribution of p k , the probability associated with the k th bin. The Ο(N −2 ) term is always negative, and minimal in the absolute sense for the uniform distribution: Ο(N −2 ) uniform = (1-K 2 )/(N 2 12 ln(2)).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…-Percent of count -Estimated Shannon entropy [35][36][37] To analyze the precision of the estimated Shannon entropy values, the standard deviation was also calculated [38]. This enabled us to assess the spread of the estimated entropy over the number of possible responses to a question:…”
Section: Analysis Methodsmentioning
confidence: 99%